Personal finance - Callaghan, George S.; Fribbance, Ian; Higginson, Martin (Palgrave Macmillan, 2012)
Personal Finance" is an innovative new book aimed atanyone who would like to build ability in making financial decisions. It distills important but complex concepts into useable form and relates them to actual experience. Written by a team of specialists, this is a "must have" book for anybody that wants their money to work as hard as they do.